Dipeptidyl peptidase-4 cell surface expression marks an abundant adipose stem/progenitor cell population with high stemness in human white adipose tissue. (31st December 2022) - Hatzmann, Florian M; Großmann, Sonja; Waldegger, Petra; Wiegers, G Jan; Mandl, Markus; Rauchenwald, Tina; Pierer, Gerhard; Zwerschke, Werner
ABSTRACT: The capacity of adipose stem/progenitor cells (ASCs) to undergo self-renewal and differentiation is crucial for adipose tissue homoeostasis, regeneration and expansion. However, the heterogeneous ASC populations of the adipose lineage constituting adipose tissue are not precisely known. In the present study, we demonstrate that cell surface expression of dipeptidyl peptidase-4 (DPP4)/cluster of differentiation 26 (CD26) subdivides the DLK1 − /CD34 + /CD45 − /CD31 − ASC pool of human white adipose tissues (WATs) into two large populations. Ex vivo, DPP4 + ASCs possess higher self-renewal and proliferation capacity and lesser adipocyte differentiation potential than DDP4 − ASCs. The knock-down of DPP4 in ASC leads to significantly reduced proliferation and self-renewal capacity, while adipogenic differentiation is increased. Ectopic overexpression of DPP4 strongly inhibits adipogenesis. Moreover, in whole mount stainings of human subcutaneous (s)WAT, we detect DPP4 in CD34 + ASC located in the vascular stroma surrounding small blood vessels and in mature adipocytes. We conclude that DPP4 is a functional marker for an abundant ASC population in human WAT with high proliferation and self-renewal potential and low adipogenic differentiation capacity.